2019
DOI: 10.1590/1519-6984.186394
|View full text |Cite
|
Sign up to set email alerts
|

Does intensive feeding frequency affect growth performance of common snook Centropomus undecimalis (Bloch, 1792)?

Abstract: Salt water recirculation systems using automatic feeders are a new frontier for marine aquaculture. It is possible to decrease the vulnerability of the traditional fish farming in open systems and reduce wasteful feeding and discharge of effluents, as well as increase the economic returns. An experiment with common snook fingerings (4.31 ± 1.42 g and 8.4 ± 1.0 cm) was performed. Three feeding treatments were evaluated: six, twelve and eighteen feeding times per day. Each treatment had three replications. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…Several studies have demonstrated that the significant increase in the feeding frequency can worsen the feed conversion. Higher feeding frequencies for the common snook ( C. undecimalis ) resulted in a poor feed conversion (Herrera et al, ). Jeong, Kayano, Oda, and Nakagawa () observed that in the Asian grouper, Epinephelus akaara (Temminck & Schlegel, 1842), a higher feeding frequency resulted in the worsening of feed conversion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated that the significant increase in the feeding frequency can worsen the feed conversion. Higher feeding frequencies for the common snook ( C. undecimalis ) resulted in a poor feed conversion (Herrera et al, ). Jeong, Kayano, Oda, and Nakagawa () observed that in the Asian grouper, Epinephelus akaara (Temminck & Schlegel, 1842), a higher feeding frequency resulted in the worsening of feed conversion.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the productive performance of the flounder Platichthys flesus luscus , using frequencies between one and four times a day, distributed in the period from 8:00 a.m. to 5:00 p.m., no advantages were observed when increasing feeding frequency (Kuçuk et al, ). However, significant results with arrowhead C. undecimalis were obtained by increasing the feeding period for 24 hr, with an improvement in productive performance (Herrera et al, ). Our results with the dusky grouper demonstrated the effective benefit of extending the period where the food should be distributed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aquaculture is an activity that has been growing in different countries given the potential for using the waters in food production (Herrera et al, 2019). Feeding protocols involving different feed deprivation and satiation cycles have been assessed in fish farming in order to achieve full compensatory growth for the species (Cotrim et al, 2016; Ortiz et al, 2008).…”
Section: Parameters Daily Feed Feed Deprived Five Days Of Feeding Two Days Of Fasting (5 × 2) Eight Days Of Feeding Four Days Of Fasting mentioning
confidence: 99%